Fluorescent pseudomonads in the rhizosphere of plants and their relation to root exudates - Vančura, Vlastimil (Folia microbiologica, 1980)
Fluorescent pseudomonads were present in chernozem soil not influenced by plant roots (10(3)-10(4) per g dry soil) in the rhizosphere soil of various plants (10(4)-10(5) per g soil) and on roots (10(3) to 10(7) per g fresh roots), depending on the species and age of the plant. Relative species representation of fluorescent pseudomonads changed on the roots and in the plant rhizosphere as compared with free soil. Pseudomonas fluorescens, representing 60-93% of the population of fluorescent pseudomonads predominated on the roots of all plants investigated. Somewhat different results were obtained in rhizosphere soil. Relatively higher numbers of P. fluorescens were detected in the rhizosphere soil of cucumber and maize, numbers in the rhizosphere soil of wheat were practically the same as in free soil and higher numbers of P. putida were found in the rhizosphere soil of barley. Almost all components contained in the root exudates of the plants studied, including beta-pyrazolylalanine from the root exudates of cucumbers were utilized as carbon and energy sources. Root exudates of wheat and maize were utilized by the strain P. putida K2 with an efficiency of 73-91%, depending on species and age of the plant.
Keywords: Plants; Zea mays; zelenina; Vegetables; Triticum; ječmen (rod); kukuřice setá; pšenice; Hordeum; Pseudomonas fluorescens; rostliny; půdní mikrobiologie; Soil Microbiology